(untitled) (Sciences & Technologie. B, Sciences de l’ingénieur, 2003)
Velocities and dispersivities are both pre-requisite in view to simulate tracer or contaminant spreading in the field as a dispersion phenomenon. Moreover they should be determined under field conditions. According to these premisses, we conducted two experiments to perform their measurements. The first one consisted of injecting water in the flow field from a well and then observing evolution towards the new steady state. The hydraulic diffusivity was evaluated by fitting the experimental heads h(r,t) to the computed ones. Once the injection cutoff we supposed all water discharging in the aquifer originates from the well in view to deduce the hydraulic conductivity and the the specific yield . Then the velocity was computed directly on use of Darcy’s equation. The second experiment is a single well injection test with two observation wells. It was monitored by measuring the electrical resistivity of the salt tracer in the piezometers. Horizontal dispersivity is determined by adjusting experimental and numerical data.The value thus obtained is close to the one estimated with the analytical models. Transverse dispersivity is computed with the semi-analytical formulae.